Challenges, Lessons, and Prospects for Operationalizing Regional Projects in Asia: Legal and Institutional Aspects - Uprety, Kishor (World Bank, 2015)
Despite efforts made by the international development financing organizations, the structure of intervention through multi-country projects with regional development goals has not been easy to design and implement. One of the reasons is the lack of clarity in the enabling legal framework and tools, both within the client countries as well as the development organizations. Against this backdrop, this study, based essentially on desk research, with limited field consultation, attempts to discuss, primarily from a legal and institutional perspectives, the tools, prospects as well as the opportunities for designing and implementing regional projects, with particular focus on the emerging practice of the World Bank, and with a special reference to the Asia region.